Diagramación de un ruteo formal de recolección, transporte y disposición final de los residuos sólidos de la ciudad de Rioja - Vela Lopez, Weyder (2011)
Waste Rioja city, in which, there was a study ofthe most important characteristics ofthe locality with respect to the following: Status conventional system's current collection and transportation of municipal solid waste, study of the meaning of public roads, particularly streets, tattered and main avenues and peri-urban part of the city, streets length quantifying both paved and unpaved, also a study was made of outstanding both strong, moderate and mil d. Besides study was conducted and the projection of the UP A physical segmentation of the city, all with the main objective that demonstrates the proposed formulation design collection routes, transportation and disposal of solid waste generated in the Rioja city. Through this study is being made to strengthen the management of solid waste in the city of Rioja, it fits precisely phases Collection, transport and disposal of Solid Waste Final comprising system largely Solid Waste Management Rioja city. Finally with this modest research are generating the municipal management tool, detailed through the gerieration of technical documentation that demonstrates to the decision makers of current municipal administration. Also the research project I estímate the totallength ofpaved streets ofthe town ofRioja amounting to approximately 11,000 linear feet, of which only 32% are paved and the rest are unpaved streets, the same as 6820 meters is linear.